Problems Encountered In Learning Speaking And The Solving Strategies By Eleventh Graders at SMA N 5 Tebo - Titik Retno Ningsih (Cahaya Ilmu Cendekia Publisher, 2020)
Purpose of the study: The purposes of this research were to investigate the problems encountered in learning speaking and to describe students’ strategies that to solve those problems. Methodology: This research was a quantitative research with a survey approach through questionnaire. The sample of this research were 68 students of natural science class 1 and 2. The data of this research were obtained through 25 questions of the questionnaire. Main Findings: The finding showed that: 1) The problems encountered by students were four aspects ( inhibition, nothing to say, low or uneven participation, and mother tongue). Nothing to say was the problem encountered by students. 2) Students mostly used all the strategies (cognitive, meta cognitive, social, and affective strategies) to help them. The cognitive strategies was the high percentage. Novelty/Originality of this study: The novelty in this research is the strategy for student problem encountered in learning is carried out at Tebo